Profil berpikir aljabar siswa SMA dalam menyelesaikan masalah ditinjau dari gaya kognitif - Jamaluddin, Muhammad; Nisa, Roisatun (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2026)
Students’ algebraic thinking ability remains relatively low, while differences in Field Independent (FI) and Field Dependent (FD) cognitive styles have not been extensively examined in the context of solving systems of linear equations in three variables at the senior high school level. This study aims to analyze students’ algebraic thinking characteristics in terms of FI and FD cognitive styles when solving problems involving systems of linear equations in three variables. The research employed a descriptive qualitative approach involving two students, each representing FI and FD cognitive styles. Data were collected through an algebraic thinking test and semi-structured interviews, and analyzed based on indicators of modeling, generalization, abstraction, dynamic thinking, analytical thinking, and organization. The findings indicate that FI students tend to be more analytical and independent, demonstrating strong abilities in abstraction and generalization as well as efficient problem-solving strategies. In contrast, FD students exhibit more contextual and procedural thinking patterns, relying on external structures and visual representations. These findings underscore the importance of adaptive algebra instruction that accommodates students’ cognitive style differences, while also providing conceptual and pedagogical contributions to the design of adaptive algebra learning based on cognitive style variation.